The effect of self-directed learning (SDL) in higher education: Increasing student independence and achievement - Siswanto, Siswanto (Universitas Negeri Yogyakarta, 2024)
This study aimed to examine the effect of the self-directed learning (SDL) model on universities in increasing student independence and achievement. The samples used were 50 students, consisting of 25 control class students and 25 experimental class students. The results of this study show that the application of the SDL learning model can increase student independence. The independent t-test results showed a significant difference in student independence between the control and experimental groups (t = 3.76, p = 0.001), with a percentage difference in independence scores between the two groups of 25%. The experimental group that received learning using the SDL model experienced an increase in independence scores by 21.4%. The results of the data normality test using Shapiro-Wilk showed that the data used in this study were normally distributed with a significance value of 0.05 (p > 0.05). SDL has increased student independence, with the experimental group experiencing an increase in independence scores by 18 points, while the control group only increased by 3 points. The improvement in academic achievement was also noticeable, with the experimental group improving 12 points compared to the control group.